(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2024)
In India, despite the reverence for female deities, patriarchy’s hold remains strong in various fields, including diplomacy. This research aims to explore the pivotal role of women within the sphere of Indian diplomacy, tracing the historical evolution. The study relies on the qualitative method of survey of literature and analysis to highlight the achievements of Indian women diplomats and persisting hurdles, including the intersectional challenges they face. The study posits that addressing and removing the gender bias in Indian diplomacy, by viewing it through a feminist lens will yield more equitable opportunities and inclusivity. It underscores the significance of Feminist Foreign Policy (FFP), introduced by Swedish foreign minister Margot Wallstrom in 2014, as a potential solution to dismantle the patriarchal bias in Indian diplomacy. Empowering women to transcend the constraints imposed by a patriarchal framework, can enhance their individual well-being and psychological fortitude, fostering an improved work culture that attracts more women to join the Indian diplomatic services. This study gives suggestive measures to improve the work-life balance and enrich the professional as well as personal lives of women in Indian diplomacy by adopting feminist ideals. The research will contribute to the broader scholarship on gender and diplomacy, which is a relatively nascent but rapidly growing research area.